2022
DOI: 10.34172/hmj.2022.07
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intervention Based on Protection Motivation Theory on Treatment Adherence in Patients with Ischemic Heart Disease

Abstract: Background: Patients with ischemic heart disease (IHD) gradually reduce their follow-up treatment due to the vulnerable physical condition and high involvement with the disease-related treatment process. The purpose of this research was to investigate the effect of intervention based on the protection motivation theory (PMT) on treatment adherence in patients with IHD. Methods: This quasi-experimental research used a pretest-posttest design with a control group. The statistical population included all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This finding is compatible with the findings of studies by Mirkarimi et al, Sanaie et al, and Posht-Chaman et al (4,11,12). A study by Zakipour et al showed that teaching proper nutrition, self-care skills, and relaxation exercises based on the protection motivation theory effectively improved self-care in patients with ischemic heart disease (18). Habibzadeh et al also reported that implementing the Health Belief Model could significantly increase the mean scores of all components of treatment adherence in patients with CAD.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is compatible with the findings of studies by Mirkarimi et al, Sanaie et al, and Posht-Chaman et al (4,11,12). A study by Zakipour et al showed that teaching proper nutrition, self-care skills, and relaxation exercises based on the protection motivation theory effectively improved self-care in patients with ischemic heart disease (18). Habibzadeh et al also reported that implementing the Health Belief Model could significantly increase the mean scores of all components of treatment adherence in patients with CAD.…”
Section: Discussionsupporting
confidence: 89%
“…[ 13 ] Previous studies have shown that both factors that make up the theory with high power are able to predict a person's intentions and behavior; especially, the coping appraisal factor and the self-efficacy component provide a strong prediction of a person's behavior. [ 1 15 ] PMT has been used in various studies to prevent a behavior, for example, to prevent risky behaviors such as acquired immunodeficiency syndrome (AIDS),[ 16 ] cardiovascular disease,[ 17 18 19 ] Ebola infection,[ 20 ] corona virus,[ 21 ] coronavirus vaccination. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%